Association of ambient temperature and acute heart failure with preserved and reduced ejection fraction. (19th June 2022) - Jimba, Takahiro; Kohsaka, Shun; Yamasaki, Masao; Otsuka, Toshiaki; Harada, Kazumasa; Shiraishi, Yasuyuki; Koba, Shinji; Takei, Makoto; Kohno, Takashi; Matsushita, Kenichi; Miyazaki, Tetsuro; Kodera, Satoshi; et al.
Abstract: Aims: Evidence on the association between ambient temperature and the onset of acute heart failure (AHF) is scarce and mixed. We sought to investigate the incidence of AHF admissions based on ambient temperature change, with particular interest in detecting the difference between AHF with preserved (HFpEF), mildly reduced (HFmrEF), and reduced ejection fraction (HFrEF). Methods and results: Individualized AHF admission data from January 2015 to December 2016 were obtained from a multicentre registry (Tokyo CCU Network Database). The primary event was the daily number of admissions. A linear regression model, using the lowest ambient temperature as the explanatory variable, was selected for the best‐estimate model. We also applied the cubic spline model using five knots according to the percentiles of the distribution of the lowest ambient temperature. We divided the entire population into HFpEF + HFmrEF and HFrEF for comparison. In addition, the in‐hospital treatment and mortality rates were obtained according to the interquartile ranges (IQRs) of the lowest ambient temperature (IQR1 <5.5°C; IQR25.5–13.3°C; IQR3 13.3–19.7°C; and IQR4 >19.7°C). The number of admissions for HFpEF, HFmrEF and HFrEF were 2736 (36%), 1539 (20%), and 3354 (44%), respectively. The lowest ambient temperature on the admission day was inversely correlated with the admission frequency for both HFpEF + HFmrEF and HFrEF patients, with a stronger correlation in patients with HFpEF + HFmrEF ( R 2 = 0.25 vs. 0.05, P < 0.001). In the sensitivity analysis, the decrease in the ambient temperature was associated with the greatest incremental increases in HFpEF, followed by HFmrEF and HFrEF patients (3.5% vs. 2.8% vs. 1.5% per −1°C, P < 0.001), with marked increase in admissions of hypertensive patients (systolic blood pressure >140 mmHg vs. 140–100 mmHg vs. <100 mmHg, 3.0% vs. 2.0% vs. 0.8% per −1°C, P for interaction <0.001). A mediator analysis indicated the presence of the mediator effect of systolic blood pressure. The in‐hospital mortality rate (7.5%) did not significantly change according to ambient temperature ( P = 0.62). Conclusions: Lower ambient temperature was associated with higher frequency of AHF admissions, and the effect was more pronounced in HFpEF and HFmrEF patients than in those with HFrEF.